2014
DOI: 10.1371/journal.pone.0089520
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Quercetin on the Development of Preimplantation Mouse Embryos against Hydrogen Peroxide-Induced Oxidative Injury

Abstract: Quercetin, a plant-derived flavonoid in Chinese herbs, fruits and wine, displays antioxidant properties in many pathological processes associated with oxidative stress. However, the effect of quercetin on the development of preimplantation embryos under oxidative stress is unclear. The present study sought to determine the protective effect and underlying mechanism of action of quercetin against hydrogen peroxide (H2O2)-induced oxidative injury in mouse zygotes. H2O2 treatment impaired the development of mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
40
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 43 publications
8
40
1
Order By: Relevance
“…In agreement to our results, Yu et al (2014) reported that the low-dose quercetin exposure (1 mM) provided mild protection by an increase in the percentage of embryos that reached the morula stage. With a concentration of quercetin up to 5 mM, blastocyst formation was recovered to levels of the control group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement to our results, Yu et al (2014) reported that the low-dose quercetin exposure (1 mM) provided mild protection by an increase in the percentage of embryos that reached the morula stage. With a concentration of quercetin up to 5 mM, blastocyst formation was recovered to levels of the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, quercetin has contradictory roles -prooxidant or antioxidant depending on the experimental situation and dose (Yu et al, 2014). It is documented that high concentration of ROS may result in oxidative damage which subsequently causes apoptotic cell death in various cell types (Bayir et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, quercetin protects Caco-2 cells against mitochondrial damage [39]. It is also reported that quercetin provided stable mitochondrial function by modulating cellular antioxidant defense and decreasing ROS in mouse zygotes [25]. In this study, quercetin showed strong antioxidant effect against superoxide generation in mitochondria.…”
Section: Discussionsupporting
confidence: 49%
“…Quercetin treated cell groups showed a dramatic fall in viability over time in a dose dependent manner ( Figure 3A). However, it is worth noting that the concentration of quercetin here was much higher than the usual concentrations reportedly used in other studies [16,25]. Hence, the cytotoxic effect of quercetin for cells reported in this study can be regarded excess in amount.…”
mentioning
confidence: 50%